O problema da justiça na República de Platão e o cidadão paradigmático da Kallipolis - Botelho, Ilíada Santos (2021)
The thesis presented aims to investigate the problem of justice and the Platonic proposal to analyze the consequences of that problem in a city that sees itself poorly managed. The problem will be treated from the conceptions of justice presented in the Republic: the myth-poetic vision and the reality of justice within the scope of governments. Plato's answer to the question posed involves the relationship between city and citizen as pillars of a better life within the community. The foundation for a better life will be found in the philosopher's educational proposal. This investigation will try to explore the problem highlighted in two ways: on the one hand, the aspects related to human nature in its relationship with justice, when confronted with a better life. On the other hand, the theme of education will be dealt with in terms of both the criticisms directed towards it, as well as what may come not only to supplant them, but also to serve the purpose of a better managed city. The central question of this thesis is to know if there is, in the educational proposal of the Republic, a theory that addresses the preparation of man, whose basis is rooted in a justice which this man is able to practice. As a hypothesis, we admit the existence of a paradigmatic citizen, modeled by Plato, which can be traced back to the education of the human soul, together with the desire for cooperation, in the love for the good of all rooted in the philia as well as the love for wisdom and friendship with fellow citizens. The heuristic method to be used in this study is the literature review together with some Platonic dialogues. This thesis is structured in four chapters, which will be developed as follows: in the first, we will deal with the conceptions of justice. In the second, we will introduce the thematic man-city-citizen. In the third chapter, we will try to prove the hypothesis of a model citizen, within the Platonic ideal as the foundation of a better life. There, the discussion of the problematic of the tyrannical soul that also leads to tyrannical government and its consequences will be expanded.